2011
DOI: 10.4103/0019-5154.91829
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of cicatricial alopecias

Abstract: Background:Cicatricial alopecias have a significant impact on the psychological status, quality of life, and social interaction of those suffering from it. Till date, limited or no data have been available regarding the psychosocial and quality of life aspects of cicatricial alopecias.Aims:To assess the psychosocial impact of cicatricial alopecias.Materials and Methods:Thirty patients fulfilling the criteria for cicatricial alopecia irrespective of their age and sex were included in the study. Psychosocial ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This probably results from the poorer prognosis of PCAs, their irreversible outcomes, and less effective treatments compared with nonscarring alopecias, such as AA. In another study by Pradhan et al (2011) , among 30 cases with cicatricial alopecia using a modified version of the Women’s Androgenetic Alopecia QoL Questionnaire, the QoL of 73.9% of patients was moderately to extremely affected, which is similar to our findings. In a publication by Chiang et al (2015) in 92 patients with PCAs in Manchester, United Kingdom, the mean DLQI score was 6.66 and 38% of patients were affected moderately to extremely.…”
Section: Discussionsupporting
confidence: 90%
“…This probably results from the poorer prognosis of PCAs, their irreversible outcomes, and less effective treatments compared with nonscarring alopecias, such as AA. In another study by Pradhan et al (2011) , among 30 cases with cicatricial alopecia using a modified version of the Women’s Androgenetic Alopecia QoL Questionnaire, the QoL of 73.9% of patients was moderately to extremely affected, which is similar to our findings. In a publication by Chiang et al (2015) in 92 patients with PCAs in Manchester, United Kingdom, the mean DLQI score was 6.66 and 38% of patients were affected moderately to extremely.…”
Section: Discussionsupporting
confidence: 90%
“… 1 Cicatricial alopecia can produce some disfigurement and psychosocial disturbances. 2 It is divided into primary and secondary types. In primary cicatricial alopecia (PCA), the hair follicle itself is the target for inflammation and destruction, whereas in the secondary type, pathological changes begin from non-follicular dermis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our descriptive pooling of patients in different severity grades showed that more than 70% of the patients with cicatricial alopecia had an impaired quality of life. Pradhan et al 18 also arrived at a similar conclusion using the Women's Androgenetic Alopecia Quality of Life Questionnaire (WAA-QOL) to measure the psychosocial impact of cicatricial alopecia (primary and secondary) on 23 patients (age range: 5-65) and found a moderate to severe life quality impairment in 73.9% of the patients. Krüger, 24 using a hair-specific life quality tool Hairdex, 34 found that patients with cicatricial alopecia have a worse quality of life than other forms of alopecia in all aspects.…”
Section: Discussionmentioning
confidence: 84%
“…From the remaining 128 articles, 14 were deemed eligible to be included in our systematic review after full‐text screening (Figure 1). A study by Pradhan et al 18 also documented the QoL in cicatricial alopecia. However, they studied both primary and secondary cicatricial alopecia and did not exclude patients under 18 (age range 5–65); hence, it was not considered for the review.…”
Section: Resultsmentioning
confidence: 98%